2009
DOI: 10.1007/s10570-009-9278-0
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of xyloglucan in water/alcohol systems by molecular dynamics simulation

Abstract: Xyloglucan in water solution turns into a gel with addition of alcohol such as methanol and ethanol. In regard to this phenomenon, we investigated the adhesive property of alcohol to xyloglucan and proposed the mechanism of the gelation by molecular dynamics (MD) simulation of a xyloglucan in water, water/methanol, and water/ethanol solution for 10 ns. The alcohol molecules showed its adhesive property to the xyloglucan and made the swellingshrinking motion of the xyloglucan slow. Alcohol molecules solvated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Hemicelluloses, like polysaccharides, contained many hydroxyl groups that form hydrogen bonds with the water molecules. When ethanol is added, it adheres to the polysaccharides through hydrophobic interactions and rearranges hydrogen bonds between water and ethanol, resulting in the possibility for the polysaccharide chains to set hydrogen bonds between each other, thus inducing their precipitation [84,85].…”
Section: Ethanol Additionmentioning
confidence: 99%
“…Hemicelluloses, like polysaccharides, contained many hydroxyl groups that form hydrogen bonds with the water molecules. When ethanol is added, it adheres to the polysaccharides through hydrophobic interactions and rearranges hydrogen bonds between water and ethanol, resulting in the possibility for the polysaccharide chains to set hydrogen bonds between each other, thus inducing their precipitation [84,85].…”
Section: Ethanol Additionmentioning
confidence: 99%
“…Observations from molecular modeling simulations using an example galactoxyloglucan oligosaccharide [123,124] may help explain some of the aggregation behavior observed for cranberry xyloglucans during chromatographic separations with alcohol-water solvent mixtures. The xyloglucan used for modeling studies [123,124] was composed of a 12-unit β-(1→4)-linked glucosyl main chain substituted with α-(1→6)-xylosyl side chains that were either unsubstituted or further substituted with β-(1→2)-galactose. When fully solubilized in water, the model galactoxyloglucan was found to prefer a twisted conformation where the side chains stabilized the backbone through inter-residue hydrogen bonds [123].…”
Section: Chromatographic Resolution and Aggregation Behaviormentioning
confidence: 99%
“…When 23.6% ethanol was added to the simulation [124], it was found that ethanol molecules aggregated around the xyloglucan structure, effectively displacing water molecules and slowing the shrinking-swelling motion of the xyloglucan that normally occurs in water-only solution [123]. The side chain interactions that stabilized the twisted backbone conformation were apparently unaffected by the addition of ethanol.…”
Section: Chromatographic Resolution and Aggregation Behaviormentioning
confidence: 99%
“…The procedure yielded 99 papers124–222 in which a classical FF, which was not necessarily a CarbFF, was applied to a carbohydrate. Studies that considered only DNA or RNA were excluded.…”
Section: A Survey Of Recent Applicationsmentioning
confidence: 99%
“…These substance‐directed applications varied more than the biologically relevant ones. Among others, there are studies targeting phase transitions,140,141 Raman and IR activity,214,221 gel formation,175 spontaneous organizations,222 and behaviors of cellulose polymers when pulled upon by the probe tip in an atomic force microscope 181…”
Section: A Survey Of Recent Applicationsmentioning
confidence: 99%